The role of the structure of the lamina cribrosa in the diagnosis and treatment of glaucoma. Structural and circulatory changes in the lamina cribrosa with aging and elevated intraocular pressure - Kurysheva, N I; Kim, V Yu; Kim, V E; Plieva, Kh M (Vestnik oftal'mologii, 2025)
The earliest damage in glaucoma starts in the posterior pole of the eye, where the axons of retinal ganglion cells, that form the optic nerve fibers, and retinal vessels pass through the connective tissue network called the lamina cribrosa (LC). Modern diagnostic techniques, such as optical coherence tomography (OCT), enable the visualization of the LC and the assessment of blood flow within it, providing new opportunities for the diagnosis of glaucoma. This review highlights the anatomy and vascularization of the LC, along with the latest research findings obtained via OCT. The article details age-related changes in the LC and the impact of intraocular pressure (IOP) changes on its properties. A novel parameter, the lamina cribrosa curvature index (LCCI), reflecting LC deformation, has been shown to be the most important biomarker of glaucomatous damage.